PENGARUH PERSEPSI HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN (STUDI PADA PELANGGAN KARTU PRABAYAR SIMPATI DI PEKALONGAN) (Jurnal Mahasiswa Pasca Sarjana, 2015)
To be able to develop customer loyalty, companies need to know the factors that influence loyalty and assess the performance of these factors. Therefore, this study intends to examine the factors that affect customer loyalty. These factors are: product quality, perceived price, and customer satisfaction. Data on product quality, price perception, and customer satisfaction is obtained through interviews using a questionnaire to customers prepaid cards SimPATI of PT Telkomsel in Pekalongan. The data obtained are then analyzed using multiple regression test. The test results of multiple regression showed that the perception of the price proven significant positive effect on customer satisfaction, product quality proven significant positive effect on customer satisfaction, customer satisfaction proven significant positive effect on customer loyalty, perception of price proven significant positive effect on customer loyalty, and quality products proven significant positive effect on customer loyalty.While the results of testing the effect of intervening indicate that the influence of the perception of price on loyalty mediated by customer satisfaction tend to influence directly the perception of price to customer loyalty mediated by customer satisfaction and influence product quality to loyalty mediated by customer satisfaction tend indirect influence product quality to customer loyalty through customer satisfaction. Keywords: perception of price, product quality, customer satisfaction, customer loyalty